ManMade - Nguyen Thi, Kim Cuong (2015)
ManMade is a short Visual Effect combined with 3D Animation film exploring the adaptation of sea creatures under the impact of pollution and environmental changes. Hindering underneath the tranquil surface of the ocean is a mysterious world that mankind never understand thorough. Deep water is the home to thousands of species. Birth. Growth. Death. They repeat the cycle of life until the day human made their first contact with their world. We as human beings grant ourselves the right to utilise the resource from the mother Earth including the sea not only to feed ourselves but also destroyed other species’ habitat. We discharge unwanted stuff into the vast sea and hope that the vast sea will bury our secret under their deepness without harming anyone. However, fish and sea birds are seriously endangered by the irresponsibility of human beings because they cannot identify the different between plastic and edible food, which will lead them to death. What if one day they really can adapt with the harsh environment and transform into a half organic and half machinery/plastic/artificial creature. Through the lens of a young and mighty boy who diving into the deep water in the short film, the audiences can observe a different world of the deep sea with eccentric creatures.